Estimation of Magnesium in Water by Flame Atomic Emission Method in Some Water Areas of Babylon Governorate - Bozhin Rahim Muhamad; Abbas Hamoudi Hanoun; Ahmed Abbas Saleh Abd Ali (American Journal of Botany and Bioengineering, 2025)
Magnesium is an essential element and an important mineral that plays a vital role in numerous bodily functions. It is necessary for maintaining muscle relaxation, proper nerve functioning, and regular heartbeats, as well as facilitating the blood clotting process. This significant mineral is recommended for daily intake to help maintain overall well-being and promote a sense of calm throughout the day. However, it is critical to be aware that excessive consumption of magnesium can lead to complications by inhibiting the absorption of other vital elements. The accumulation of these elements in the body can eventually reach toxic levels, posing serious health risks. Therefore, it is important to establish a distinct quality assurance standard to ensure that the levels of this mineral do not exceed safe limits in drinking and irrigation water. This study thoroughly examined the infringement of maximum concentration levels of magnesium in various locations throughout the Babylon Governorate. This research is essential not only for environmental integrity but also for safeguarding public health and ensuring the safety of the community.